Ischaemic stroke patients with heterozygous factor V Leiden present with multiple brain infarctions and widespread atherothrombotic disease - Haapaniemi, Elena; Helenius, Johanna; Jakovljeviâ, Dimitrije; Soinne, Lauri; Syrjälä, Martti; Kaste, Markku; Lassila, Riitta; Tatlisumak, Turgut (Thrombosis and Haemostasis, 2009)
Factor V Leiden (FVL) mutation is a risk factor for venous and, to a degree, arterial thrombosis. It is unknown whether and how FVL affects the manifestations of ischaemic stroke (IS). We assessed the clinical, laboratory, radiological, and prognostic characteristics in an observational study with adult IS patients having FVL. We tested 860 patients with first-ever IS for FVL and found 48 FVL positive patients. Detailed clinical, laboratory, and radiological evaluation were compared with that of 144 (1:3) gender and age matched IS patients without FVL. All patients underwent a prognostic evaluation at an average of five years follow-up. Despite the relatively young age (mean 48.5 years, range 44–54 years) of the FVL positive IS patients, peripheral arterial occlusive disease (PAOD), coronary artery disease (CAD), and previous transient cerebrovascular event occurred more frequently compared with controls. Family history of cardiovascular disease (CVD) and multiple silent brain infarctions were revealed in half of the FVL positive patients, whereas these were seldom encountered among controls. Stroke severity, long-term recovery, and recurrence rates seemed similar irrespective of FVL status. Our findings indicate that the clinical profile of IS patients with FVL associated with wider manifestation of atherothrombosis, positive family history of arterial thrombosis, and presence of multiple silent infarctions on brain images.
Keywords: Factor V Leiden mutation; ischaemic stroke; coagulation; cardiovascular disease; peripheral arterial occlusive disease